Analisis Literasi Keuangan Dalam Meningkatkan Perkembangan Usaha Pada Rumah Produksi Cekeremes Mbok Kaseh - Nur Arista, Arini; Hakiki, Nurul; Anita, Lella; Anggara, Berwin (Jurnal Media Informatika, 2024)
This study aims to analyze financial literacy in UMKM, with a focus on Cekeremes Mbok Kaseh Production House. The approach used in approach used in this research is descriptive qualitative, in which data is collected through in-depth interviews with business owners and direct observation of operational activities. The results showed that the level of financial literacy financial literacy level of UMKM owners is still inadequate. This can be seen from the absence of systematic financial records, such as income statements and balance sheets, as well as a lack of understanding of cash flow management and long-term financial planning. The results of the research and observations show that the level of financial literacy of UMKM owners is still inadequate. financial literacy level of UMKM owners is still inadequate. This is reflected in the lack of understanding of systematic financial planning, efficient cash management, and difficulties in accessing financing. efficient cash management, and difficulties in accessing appropriate financing and employment aspects. This has a significant impact on their ability to grow their businesses. develop their business. Thus, this study concludes that better financial literacy is needed to improve the sustainability and growth potential of MSMEs such as the and growth potential of UMKM such as Cekeremes Mbok Kaseh Production House